A Qualitative Assessment to Understand the Barriers and Enablers Affecting Contraceptive Use Among Adolescent Male Emergency Department Patients. Issue 1 (February 2019) - Chernick, Lauren S.; Siden, Jonathan Y.; Bell, David L.; Dayan, Peter S.
Early fatherhood is common in the United States (U.S.). The emergency department (ED) plays a disproportionate role in serving patients with unmet reproductive and sexual health needs. With 8 million adolescent males visiting U.S. EDs annually, the ED is a potential site to implement interventions to minimize early fatherhood and unintended teenage pregnancy. Little is known about how adolescent male ED patients perceive and behave in sexual relationships and how they influence contraceptive decision making. The objective of this study was to identify the barriers and enablers affecting contraceptive and condom use among adolescent male ED patients. Semistructured interviews were conducted with males aged 14–19 in one urban ED. Enrollment continued until saturation of key themes. Interviews were recorded, transcribed, and coded based on thematic analysis using NVivo 10. The Social Ecological Model was used to organize and understand themes. Participants ( n = 24) were predominantly 18–19 years (63%) and Hispanic (92%). Most (71%) had sex ≤3 months prior but infrequently used a condom at last intercourse (42%). The primary barrier influencing contraceptive use was lack of knowledge of effective contraceptives. Other barriers consisted of perceived gender roles, poor partner communication, and little relationship with a primary provider. Enablers included intention not to get a partner pregnant, school-based sexual health education, normalcy to use condoms, and a trustworthy confidante. The identified barriers and enablers influencing adolescent males' perspectives toward contraceptives should be addressed if designing future ED-based pregnancy prevention interventions targeting teen males.